Anaesthesia considerations in a case of Morquio syndrome with bilateral mechanical vertebral artery occlusion: a case report - Nagtilak, Harshada Hanamant; Shah, Nishita; Daftary, Swati; Mehta, Hemant (International Journal of Research in Medical Sciences, 2021)
Morquio syndrome (MS) or mucopolysaccharidosis (MPS) type IVA is a progressive lysosomal storage disorder with autosomal recessive inheritance. Deficiency of enzymes N-acetyl-galactosamine-6-sulphatase and beta-galactosidase which compromises the catabolism of the glycosaminoglycans (GAGs) leads to excessive accumulation of GAGs in soft tissue, cartilage and bone causing severe skeletal dysplasia and difficult airway. Other systems commonly involved systems are cardiovascular, respiratory, neurological, ophthalmological, otolaryngological and hepatosplenic. Most of the patients with MPS survive up to second or third decade only. We present a case of 7 years old male child, known case of Morquio syndrome who presented with acute cerebral arterial stroke due to bilateral mechanical vascular occlusion of vertebral artery, posted for occipito-cervical fusion. Understanding Morquio syndrome, its airway and the anesthetic implications and careful planning of the anesthetic technique enabled us to manage this patient successfully.